Tautomerism : methods and theories - Antonov, Liudmil (Weinheim, Germany : Wiley-VCH, 2014)
"Covering the gap between basic textbooks and over-specialized scientific publications, this is the first reference available to describe this interdisciplinary topic for PhD students and scientists starting in the field. The result is an introductory description providing suitable practical examples of the basic methods used to study tautomeric processes, as well as the theories describing the tautomerism and proton transfer phenomena. It also includes different spectroscopic methods for examining tautomerism, such as UV-VIs, time-resolved fluorescence spectroscopy, and NMR spectroscopy."--Publisher's website.
3.3.3 Advanced Techniques in Fluorescence Spectroscopy; 3.3.3.1 Fluorescence Anisotropy; 3.3.3.2 Fluorescence Microscopy and Fluorescence Correlation Spectroscopy; 3.4 Tautomerism in Bifunctional NH/N Azaaromatics; 3.4.1 Intramolecular NH/N Tautomerization; 3.4.2 Intermolecular NH/N Tautomerization in Hydrogen-Bonded Dimers; 3.4.3 Tautomerization in Solute-Solvent Hydrogen-Bonded Complexes; 3.5 Ab initio and DFT Computational Methods; 3.5.1 Reaction Mechanisms and Cooperativity in Proton Migrations; 3.5.1.1 Concerted versus Stepwise Mechanism.
3.5.2 Reaction Path Calculations and Energy Barriers for Proton Transfer.
Includes bibliographical references (pages 395-403) and index.
Online resource; title from PDF title page (Wiley, viewed November 12, 2013).
Keywords: Tautomerism; SCIENCE -- Chemistry -- Physical & Theoretical; Tautomerism; Science; Electronic books; Electronic books